The Body Politic as a Sacred Vessel: A Systematic Review of the Cross-Cultural Resonance of Moral Metaphors - Belay Sitotaw Goshu; Muhammad Ridwan (LingLit Journal Scientific Journal for Linguistics and Literature, 2025)
Unfilled pauses silent gaps in conversation carry pragmatic meaning that may vary across cultural contexts. Hall’s (1976) distinction between high context (HC) and low context (LC) cultures suggests that silence is valued in HC societies as a sign of reflection and respect, whereas LC societies interpret silence as evasive or uncomfortable. However, empirical evidence directly linking pause duration to Hall’s dimension in naturalistic and experimental settings remains limited. This study investigated cross cultural differences in the production and interpretation of unfilled pauses. Specifically, we examined whether HC speakers produce longer and more frequent pauses, and whether listeners from HC versus LC cultures differentially rate willingness, politeness, and competence as a function of pause length. Phase 1 corpus analysis (Japanese, Egyptian Arabic, German, American English; N = 400 conversations) revealed that HC speakers produced pauses nearly twice as long (mean = 915 ms) and twice as frequent as LC speakers (mean = 517 ms). Phase 2 experimental results (N = 480) showed a significant interaction between pause duration and cultural group for willingness ratings, F(3, 19152) = 34.7, p < .001. LC listeners’ willingness dropped 52% from short to long pauses, while HC listeners dropped only 15%. For politeness, longer pauses increased ratings for HC listeners but decreased them for LC listeners. Unfilled pauses function as a culturally variable pragmatic marker, supporting Hall’s high /low context framework and challenging Universalist accounts of silence interpretation. Intercultural communication training should explicitly address pause norm differences, and pragmatic competence assessments in second language learning should incorporate culturally appropriate silence use.